Avaliação dos efeitos do citrato de sódio sobre o metabolismo lipídico e da acetilcolina em camundongos - Balz, Daniela (2002)
The sodium citrate is one of the most utilized in chemical food additives that have been found in tinned and milk derivatives. Its proprieties are: stabilizer, emulsifier and acidity regulator. The chemical compound can be dissociated in water by releasing its anion. The endogenous citrate in biological systems plays an important role in the general metabolism, serving as a source of acetyl-CoA that can be utilized for the synthesis of lipids and acetylcholine. The citrate also has an important role in controlling the effects on enzymes as Phosphofructokinase and Acetyl-CoA carboxylase. The aims of this study are the investigations on the effects of the additive over lipid and acetylcholine metabolism together with the evaluation of biochemical parameters with ions Na+, K+, urea and creatinine. The mice were separated in two different treatments: subchronic (55 days) and chronic (110 days), males and females. The sodium citrate solutions were control (potable water), 1%, 2.5% and 5% ad libitum in drinking water. The results showed an increase of the body weight in 2.5% concentration for both subchronic and chronic treatments. In the inner organs, the study showed a decrease of livers weight in 5% concentration. In the histological analysis we observed that the animal cells in 2.5% concentration had more capacity of lipid saving, but in 5% this capacity is decreased. It was observed an increase on the quantify of muscle lipids on the male in both treatments. The lipase evaluation has shown a decrease on the subchronic males in 2.5% and 5% sodium citrate concentrations. Didn’t appear changes in K+ levels. In the ACh metabolism had an increase of AChE in the subchronic male and chronic female in vivo treatments. The in vitro experiments had a tendency for activity increasing AChE in sodium citrate 50 mM. The objective of this work was to recover aspects around the application of sodium citrate and its possible interactions in lipid metabolism and acetylcholinesterase activity.